2013
DOI: 10.3389/fimmu.2013.00179
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy, a Novel Pathway to Regulate Calcium Mobilization in T Lymphocytes

Abstract: The T lymphocyte response initiates with the recognition of MHC/peptides on antigen presenting cells by the T cell receptor (TCR). After the TCR engagement, the proximal signaling pathways are activated for downstream cellular events. Among these pathways, the calcium-signaling flux is activated through the depletion of endoplasmic reticulum (ER) calcium stores and plays pivotal roles in T cell proliferation, cell survival, and apoptosis. In studying the roles of macroautophagy (hereafter referred to as autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…As we know, the concentration of cytoplasmic free calcium usually remains very low. In response to certain stimuli, the cytoplasmic calcium level can increase sharply by release from the ER or transport from the extracellular environment [ 29 , 43 , 44 ]. Our data showed that triptolide induces ER stress in PCa cells, and the ER stress inhibitors significantly inhibit the accumulation of cytoplasmic calcium and activation of the CaMKKβ-AMPK signaling pathway in the presence of triptolide.…”
Section: Discussionmentioning
confidence: 99%
“…As we know, the concentration of cytoplasmic free calcium usually remains very low. In response to certain stimuli, the cytoplasmic calcium level can increase sharply by release from the ER or transport from the extracellular environment [ 29 , 43 , 44 ]. Our data showed that triptolide induces ER stress in PCa cells, and the ER stress inhibitors significantly inhibit the accumulation of cytoplasmic calcium and activation of the CaMKKβ-AMPK signaling pathway in the presence of triptolide.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is unlikely the reason for the increased amount of ROS that we observed in Atg5-deficient CD8 + T cells because the mitochondrial mass was comparable to that of Atg5-expressing control cells. Besides the mitochondria, the peroxisome and the endoplasmic reticulum could also serve as potential sources of ROS (17,51,52). Additionally, impaired ROS scavenging via the glutathione pathway may also explain why autophagy-deficient CD8 + T cells displayed higher levels of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy plays a key role in naive T cell homeostasis and is essential for in vitro T cell activation (15)(16)(17)(18)(19)(20)(21). Bone marrow chimera studies found that deletion of Atg5 resulted in the reduction of peripheral T and B cells (21) whereas Atg5 or Atg7 knockout impaired T cell development due to hyperaccumulation of mitochondria and reactive oxygen species (ROS) (18,22,23).…”
mentioning
confidence: 99%
“…This might be crucial to provide activated T cells with the necessary degraded intermediates for growth and proliferation. Furthermore, autophagy maintains the ER and therefore regulates calcium mobilization in activated T cells 77 . An mTOR‐independent, glycolysis‐upregulating pathway is also induced upon T‐cell activation and signals via PIM kinases and c‐Jun N‐terminal kinases 78 .…”
Section: Autophagy In Mature T Cellsmentioning
confidence: 99%